Processing Information During Regressions: An Application of the Reverse Boundary-Change Paradigm - Sturt, Patrick; Kwon, Nayoung (Frontiers in Psychology, 2018)
Although 10-15% of eye-movements during reading are regressions, we still know little about the information that is processed during regressive episodes. Here, we report an eye-movement study that uses what we call the "reverse boundary change technique" to examine the processing of lexical-semantic information during regressions, and to establish the role of this information during recovery from processing difficulty. In the critical condition of the experiment, an initially implausible sentence (e.g. "There was an old house that John had ridden when he was a boy.") was rendered plausible by changing a context word ("house") to a lexical neighbour ("horse") using a gaze-contingent display change, at the point where the reader's gaze crossed an invisible boundary further on in the sentence. Due to the initial implausibility of the sentence, readers often launched regressions from the later part of the sentence. However, despite this initial processing difficulty, reading was facilitated, relative to a condition where the display change did not occur (i.e. the word "house" remained on screen throughout the trial). This result implies that the relevant lexical semantic information was processed during the regression, and was used to aid recovery from the initial processing difficulty.